RNA splicing permits expression of a maize gene with a defective Suppressor-mutator transposable element insertion in an exon. - Kim, H Y (1987)
The bz-m13CS9 allele of the bronze-1 gene in maize contains a 902-base-pair defective Suppressor-mutator (dSpm) transposable element in the second exon. Nevertheless, 40-50% of the enzymatic activity conditioned by a nonmutant allele at the bronze-1 locus is routinely recovered in crude extracts prepared from plants carrying bz-m13CS9 in the absence of an autonomous Suppressor-mutator element. Analyses of RNAs produced by such plants show that transcription proceeds through the dSpm. The dSpm sequence of the messenger RNA precursor is then removed by RNA splicing using the donor site of the single bronze-1 intron and an acceptor site within the inverted terminal repeat of the dSpm. This results in a messenger RNA with the proper reading frame that could produce a functional enzyme. These data demonstrate that this dSpm insertion in an exon of a structural gene has produced a functional allele with a novel intron consisting, in part, of the dSpm. This mechanism appears to allow dSpm elements to reduce the impact of their insertions on gene expression.